Increased risk of musculoskeletal injury following sport-related concussion: A perception-action coupling approach - Eagle, S. R.; Kontos, A. P.; Pepping, G. J.; Johnson, C. D.; Sinnott, A.; LaGoy, A.; Connaboy, C. (Sports Medicine, 2020)
Recent studies have concluded that athletes have increased risk of musculoskeletal injury following sport-related concussion. While an underlying explanation is still unknown, perceptual-motor control may be implicated in this increased risk. Some authors have purported that indirect perception (i.e., a "top-down" view of neuromuscular control) may be disrupted following sport-related concussion. Direct perception theory states that the athlete and environment are inextricably linked in a continuous perception-action coupling loop. That is, the athlete is able to directly perceive opportunities for action (e.g., "affordances") in the environment. Based on these notions, the aim of the current paper was to introduce a theoretical model that argues that sport-related concussion may dysregulate the direct perception process, potentially increasing behavioral risk of musculoskeletal injury during sport. Our model is integrated with a sport-related concussion clinical treatment model, which highlights individualized profiles that characterize the heterogeneous response to sport-related concussion. These profiles have a typical constellation of symptoms (e.g., anxiety, fatigue, ocular dysfunction, etc.), which themselves have been associated with disrupted perception-action coupling, independent of sport-related concussion. Therefore, we argue that athletes who have not re-established perception-action coupling loops following sport-related concussion may be at increased risk of subsequent musculoskeletal injury.